INTERRELATIONS BETWEEN TAX EDUCATION, TAX COLLECTION AND ECONOMIC DEVELOPMENT IN THE INTERMEDIATE REGION OF BARBACENA (REMUNOM, 2025)
This article analyzes the relationship between tax education, tax collection, and economic development, evaluating the effects of this policy on the municipality of Barroso compared to other municipalities in the Barbacena Intermediate Region. The methodology used includes the application of a regression model with panel data for the period 2003-2019. According to the results, tax education, like tax collection, was significant in explaining the development index, but with a negative coefficient, unlike tax collection, which had a positive effect on the IDTE. However, these results do not dismiss the importance of tax education, which is an important step in municipalities to raise public awareness of the benefits that can result from fulfilling their tax obligations.